Meningkatkan Kemampuan Bahasa Lisan Anak Usia Dini Melalui Metode Bercerita Pada Anak Kelompok A - Sry Anita Rachman; Farlina Hardianti; Samsul Mujtahidin (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to develop children’s oral language skills through storytelling in Group A at PAUD KB Melati during the 2024/2025 academic year. The research employed Classroom Action Research (CAR), conducted in two cycles with collaboration between teachers and researchers. The subjects were all 25 children in Group A. Data collection techniques included observation, documentation, and field notes, using instruments such as observation sheets, field note sheets, and documentation records. Data were analyzed descriptively and qualitatively to assess the progress of children’s oral language abilities.The findings revealed significant improvement after the implementation of storytelling. Prior to the intervention, children’s participation in language learning was only 21.75%, with 6 children (20%) achieving mastery. After the first cycle, participation rose to 77.5%, with 3 children (10%) developing very well, 10 children (45%) developing as expected, 5 children (15%) beginning to develop, and 15 children (55%) reaching the expected level of development. In the second cycle, participation increased further to 83.1%, with 5 children (15%) developing very well, 15 children (55%) developing as expected, 3 children (10%) beginning to develop, and 3 children (10%) not yet developing. Overall, 19 children (80%) achieved the expected developmental outcomes. Thus, the research confirmed the hypothesis that storytelling can effectively enhance oral language skills in young children. Storytelling proved to be an effective instructional strategy, fostering greater participation, enriching vocabulary, and encouraging children to be more active in communication. This demonstrates that storytelling is not merely a form of entertainment but a pedagogical approach that systematically and enjoyably supports the oral language development of early childhood learners.